COOPERATION WITH INTERNATIONAL ORGANIZATIONS FOR MODERNIZING PUBLIC POLICY OF RISK MANAGEMENT IN CONSTRUCTION - Kharaim I.V. (Pressing Problems of Public Administration, 2018)
The paper emphasizes that cooperation with international organizations is an important aspect of theregional development strategy of every region in Ukraine. Additional opportunities for cooperation withinternational organizations are determined, in particular, in the sphere of international cooperationin construction risk management. It is pointed out that the activity of modern organizations isperformed under the conditions of risk. The author highlights the fact that risk management includessuch purpose-oriented actions as risk planning, identi cation, assessment, treatment, control anddocumentation. Under risk, there appears a need for introduction of the institution of a consultantengineer as a subject of the market of engineering services, and a general understanding of theadvantages of applying internationally recognized forms of contracts, speci cally the typical forms ofthe International Federation of Consulting Engineers (FIDIC).